Reactions of Substituted Furan-2-carboxaldehydes and Furo[b]pyrrole Type Aldehydes with Benzothiazolium Salts - Tatiana Ã„ÂŽurÃ„ÂekovÃƒÂ¡; AntonÃƒÂn LyÃ„Âka; AlÃ…Â¾beta KrutoÃ…Â¡ÃƒÂkovÃƒÂ¡; Zita PuterovÃƒÂ¡ (Molecules, 2004)
A series of new push-pull compounds were synthesised by reaction of 5-aryl- furan-2-carboxaldehydes and furo[b]pyrrole type aldehydes with benzothiazolium salts. These new condensation products represent highly conjugated systems that have potential biological activity. The reaction of furo[b]pyrrole type aldehydes with benzothiazolium salts give potential precursors of cyanine dyes.